PERAN KREDIT USAHA RAKYAT (KUR) BANK JATENG TERHADAP PERKEMBANGAN USAHA MIKRO DI KABUPATEN BOYOLALI (STUDI KASUS : NASABAH BANK JATENG CABANG BOYOLALI) - Ayuditya Widha Kurnia Sari; Nenik Woyanti (Diponegoro Journal of Economics, 2014)
ABSTRACTSince the economic crisis hit Indonesia in 1997-1998, micro enterprise  that included from micro, small and medium enterprise showed their existence to hold out when some big factories at the same time was insolvent. In additional, micro enterprise also helping the absorption of labor. But, micro enterprise still require an attention, especially in terms of capital. Micro enterprise was considered have high risk to survive in business competition if not supported by good performance. Micro enterprise in Boyolali also experience with capital constraints. It becomes an obstacle to doing business.    The purpose of this study was to analyze the differences and the development of micro enterprise in Boyolali between before and after the micro enterprise obtaining “Kredit Usaha Rakyat (KUR)” from Bank Jateng branch of Boyolali in terms of cost of production, sales turnover, profit, and hours of work. The object of this study are costumers of “Kredit Usaha Rakyat (KUR)” in Bank Jateng branch of Boyolali and total respondents are 80 people. To see the difference between before and after of the five variables that was receiving KUR from Bank Jateng branch of Boyolali are used wilcoxon sign rank test.Based on the results of Wilcoxon sign rank test result showed that the p-value of production costs of 0.000 (0.000<0.05) which means significantly increased after receiving the KUR of 33.4%. The sales turnover variables obtained p-value of 0.000 (0.000<0.05) which means that significantly increased sales turnover after receiving KUR, while the increase amounted to 47.4% occurred. Variable profit have  p-value of 0.000 (0.000<0.05), which means an increase in variable profits significantly after receiving KUR, an increase of 67.2% that occurred. The hours of work are variable p value of 0.000 (0.000<0.05), which means there is significant difference between the hours of work before and after receiving KUR with 34% to increased. So it can be seen that the increase after receiving KUR from Bank Jateng branch of Boyolali are variable production cost, sales turnover, profit, and hours of work.